STRATEGI ADAPTASI SOSIAL DAN EKONOMI (KASUS KARYAWAN-KARYAWAN DISABILITAS IKPP YANG DI PHK DI KECAMATAN TUALANG KABUPATEN SIAK) - Andreas Novhendra; Jonyanis " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
Termination of employment that occurs on employees with disabilities causing loss of their income and threatened the lives of employees with disabilities with physical disability providing barriers to them to looking for a new job. So that the employees with disabilities are hampered in their social and economic life so it needs strategy to overcoming their social and economic problems. The purpose of this study is to see how families with disabilities can fulfill their social and economic needs after they are not working anymore and aims to find out what are the dominant strategies that used by employees with disabilities and aims to know the factors of strategy selection. This study provides a detailed overview based on the facts that found in the field about social and economic adaptation strategy of employees with disabilities in Tualang Sub-district of Siak Regency with snowball technique with the sample of 5 people. The writer applied qualitative descriptive method and also observation and interview as data collection instrument. Based on the writer’s study it was found that the condition of employees with disabilities at the beginning of termination of employment many employees with disabilities become stressful because they do not have a job anymore but they do not drag on under these conditions and they rise up by using some strategy to fulfill their social and economic needs, but the dominant strategy that they used were active, network and double. These three strategies are dominantly chosen because of influenced by educational factors, association and economic. Keyword : adaptation, disability, termination of employment